Parking Zone – An Automated Parking Management System for Shopping Malls - Susy Dickrose, Drusalind Justina (IRC, 2019)
Finding empty parking lot in shopping mall is frustrating especially on public holidays. Inability to find a parking lot which is empty and inability to identify parking lot that is becoming empty soon leads to a guessing game. This game is very frustrating especially when people are in hurry. This project addressed this issue and attempted to solve it with the help of technology. The proposed system, Parking Zone is a system consists of a mobile application, a web application and IOT device to reserve parking lots with just a few clicks. While there are many parking applications to allow people pay parking fee, Parking Zone attempted to enhance the idea with the help of IOT devices and features such as advance booking. The proposed system will help people to find empty parking lots easily while also alert them when their parking period is ending soon. The system models are created by following the Unified Modeling Language (UML) and the output of this study is a prototype for the proposed system. The prototype was created using various technologies and frameworks. Web and API were created using Laravel Framework, React Native framework is used for mobile app and Arduino programming used for Arduino based IOT device which will be connected to servo for parking lot reservation.